Protection from A Quantum Computer Cyber-Attack: survey - Raya , Jasim Easa; Yahya, Asma Salim; Ahmad, Esraa Khalid (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Encryption is required to address the ongoing issue of information security within communication networks. In the second part of the 20th century, quantum computing was first utilized to crack encryption protocols with the SHOR algorithm's development. The transformation from traditional to computational has the possibility of jeopardizing the protection of the current transaction system, even though recent improvements in QC functionality have increased the privacy and security, integrity, and accessibility of networks by shielding them from attacks like eavesdropping. This research adopts a comprehensive literature review approach to clarify the effects of quantum computers on information security. In addition, the study provides a summary of current efforts to guard against quantum attacks. Examining all suggested information security and privacy safeguards, this study examines the additional issue that quantum computers would severely damage information security.